Preparation of Activated Carbon from Desiccated Coconut Residue by Chemical Activation with NaOH - Mohd Adib Yahya; C.W. Zanariah; C. W. Ngah; M. A. Hashim; Z. Al-Qodah (Canadian Center of Science and Education, 2024)
This study investigates the effect of temperature and impregnation ratio on the physicochemical properties of activated carbon prepared from agricultural waste; desiccated coconut residue (DCR) by chemical activation using sodium hydroxide (NaOH). DCR sample was first carbonized at three different temperatures for 1 hour at 400°C, 500°C, and 600°C respectively. The resulting chars were impregnated with NaOH at three different impregnation ratio; 1:1, 1:2, and 1:3 respectively and activated under nitrogen atmosphere for 1 hour at three different temperatures based on its carbonization temperature. The specific surface area was strongly affected by impregnation ratio in which increased with impregnation ratio. The specific surface area also increased with temperature but then decreased at highest desired temperature.